Integrating Christian Ethics into the Use of Digital Technology in Christian Education: A Literature Review - Melina Agustina Sipahutar; Andar Gunawan Pasaribu; Elisamark Sitopu; Lasmaria Lumban Tobing (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
The development of digital technology has transformed various aspects of human life, including education. Students now have extensive access to various digital learning resources such as e-books and instructional videos. However, a lack of understanding of digital ethics often leads to problems such as plagiarism and the spread of hoaxes. This article aims to examine how Christian ethical principles derived from the Bible can guide the use of technology in education. By integrating biblical values ​​such as love, honesty, responsibility, self-control, and wisdom, Christian education shapes not only intellectual abilities but also moral and spiritual character. The literature review shows that applying Christian ethics in the use of technology can prevent digital abuse and strengthen Christlike character in students and teachers. Thus, technology can be a means to glorify God and bring blessings to others.